Multi-band magnetotransport in exfoliated thin films of CuxBi2Se3. (16th March 2018) - Alexander-Webber, J A; Huang, J; Beilsten-Edmands, J; Čermák, P; Drašar, Č; Nicholas, R J; Coldea, A I
Abstract: We report magnetotransport studies in thin (<100 nm) exfoliated films of Cu x Bi2 Se3 and we detect an unusual electronic transition at low temperatures. Bulk crystals show weak superconductivity with T c ∼ 3.5 K and a possible electronic phase transition around 200 K. Following exfoliation, superconductivity is supressed and a strongly temperature dependent multi-band conductivity is observed for T   <  30 K. This transition between competing conducting channels may be enhanced due to the presence of electronic ordering, and could be affected by the presence of an effective internal stress due to Cu intercalation. By fitting to the weak antilocalisation conductivity correction at low magnetic fields we confirm that the low temperature regime maintains a quantum phase coherence length L ϕ > 100 nm indicating the presence of topologically protected surface states.